2012
DOI: 10.1016/j.bbr.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Tongue force and tongue motility are differently affected by unilateral vs bilateral nigrostriatal dopamine depletion in rats

Abstract: In addition to its cardinal symptoms of bradykinesia, muscle rigidity, resting tremor and postural disturbances, Parkinson’s disease (PD) also affects orolingual motor function. Orolingual motor deficits can contribute to dysphagia, which increases morbidity and mortality in this population. Previous preclinical studies describing orolingual motor deficits in animal models of PD have focused on unilateral nigrostriatal dopamine (DA) depletion. In this study we compared the effects of unilateral vs bilateral 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 47 publications
2
25
0
1
Order By: Relevance
“…The SOD1-G93A transgenic rodents are validated models of oral-stage dysphagia for bulbar deficits of Amyotrophic Lateral Sclerosis [28, 32]. There are multiple models of Parkinson’s disease, including (6-OHDA)-induced DA depletion [8, 37], surgical lesions [42] and PINK KO genetic models [22, 23]. Surgical or pharmacological models of stroke in rodents have been common, but are now being developed and validated for examining dysphagia [19, 44].…”
Section: Ceteris Paribus and Understanding Pathophysiologymentioning
confidence: 99%
“…The SOD1-G93A transgenic rodents are validated models of oral-stage dysphagia for bulbar deficits of Amyotrophic Lateral Sclerosis [28, 32]. There are multiple models of Parkinson’s disease, including (6-OHDA)-induced DA depletion [8, 37], surgical lesions [42] and PINK KO genetic models [22, 23]. Surgical or pharmacological models of stroke in rodents have been common, but are now being developed and validated for examining dysphagia [19, 44].…”
Section: Ceteris Paribus and Understanding Pathophysiologymentioning
confidence: 99%
“…Factors other than nigrostriatal DA may also play a role in age-related tongue motility deficits, however. For example, we recently reported that bilateral nigrostriatal DA depletion does not reduce tongue motility in young adult rats (Nuckolls, et al, 2012). Furthermore, our current results with GBR-12909, and our previous results with nomifensine (Stanford et al, 2003), suggest that increasing extracellular DA by blocking its reuptake does not improve tongue motility in aged rats.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study compared unilateral to bilateral dopamine depletion in a licking task akin to the one used in the current study. [34] Both unilateral and bilateral lesions caused reductions in licking force, however, only the unilateral lesion group showed deficits in tongue motility. [34] These results suggested that unilateral deficits can represent an interhemispheric imbalance in terms of sensorimotor control.…”
Section: Discussionmentioning
confidence: 99%